Pengembangan Bahan Ajar Mata Pelajaran Fikih Berbasis Problem Based Learning - Siti Murtosiah; Ichromsyah Arrochman; Sartina Sartina (Departement of Mathematics Education, 2023)
Teaching materials are one of the supports in the learning process, and are the main factor in learning success in class XII MA Al-Ittifaqiah 2 Tanjung Lubuk South Sumatra students. Problem-based learning-based teaching materials that are specifically designed are able to balance student needs so that the learning process becomes a student center with easy-to-understand material content. This type of research is research and development. And the development model that researchers apply is to use the 4-D model. The results of this study are: The product validity level based on the validation data results by the three validators is already valid and has minor revisions. At an attractive and decent level based on data it can be categorized as attractive and feasible with a total presentation of 95.2%. The effectiveness of teaching materials can be seen in the average score of the class during the pre-test with a result of 70.45 and in the pot-test with a result of 90.55. Exceeding the standard of kkm 76 in class XII, so that based on the results of the scores obtained during the post-test, it can be concluded that teaching materials in the form of problem-based learning-based LKPD are effective and suitable for use.